Effect of ZnO addition on structural properties of ZnO-PANi/carbon black thin films - Siti Fariza Mat Tahir; Norhashimah Ramli; Izura Izzuddin; Muhamad Mat Salleh; Muhammad Yahaya; Akrajas Ali Umar; Mohammad Hafizuddin Haji Jumali (Universiti Kebangsaan Malaysia, 2012)
The aim of this project was to investigate the effect of ZnO addition on the structural properties of ZnO-PANi/carbon black thin films. The sol gel method was employed for the preparation of ZnO sol. The sol was dried for 24 h at 100°C and then annealed at 600°C for 5 h. XRD characterization of the ZnO powder showed the formation of wurtzite type ZnO crystals. The ZnO powder were mixed into PANi/carbon black solution which was dissolved into M-Pyrol, N-Methyl-2-Pyrrolidinone (NMP) to produce a composite solution of ZnO-PANi/carbon black. The weight ratio of ZnO were 4 wt%, 6 wt% and 8 wt%. The composite solutions were deposited onto glass substrates using a spin-coating technique to fabricate ZnO-PANi/carbon black thin films. AFM characterization showed the decreasing of average roughness from 7.98 nm to 2.23 nm with the increment of ZnO addition in PANi/carbon black films. The thickness of the films also decreased from 59.5 nm to 28.3 nm. FESEM image revealed that ZnO-PANi/carbon black thin films have changed into agglomerated surface morphology resulting in the increment of porosity of the films.